[PP.06.06] CAN ARTERIAL WAVE AUGMENTATION IN YOUNG ADULTS EXPLAIN VARIABILITY OF CARDIOVASCULAR RISK IN ETHNIC MINORITIES?. (September 2016) - Faconti, L.; Silva, M.; Molaodi, O.; Enayat, Ze.; Cassidy, A.; Karamanos, A.; Read, U.; Dall, P.; Stanfield, B.; Harding, S.; Cruickshank, J.K.
Abstract : Objective: Traditional cardiovascular (CV) risk factors do not fully explain ethnic differences in CV disease. We tested if pulse wave velocity (PWV) and Augmentation Index (AIx), both independent predictors of later adult mortality, and their determinants from childhood may underlie ethnic variability in CV risk as young adults in the 'DASH' longitudinal study. Design and method: Details of our DASH study's longitudinal design can be found athttp://dash.sphsu.mrc.ac.uk/, DASH includes representative samples of 6 main UK ethnic groups, starting at school aged 11–13y, followed again at 14–16y, both with anthropometry, blood pressures (BP) and psychosocial measures. PWV and AIx were then recorded using the Arteriograph device at ages 21–23y in a random sub-sample (n = 666). For n = 334, physical activity (PA) was also measured over 5 days (ActivPal). Results: Unadjusted PWVs in Black Caribbean and White UK young men were similar (7.9 + 0.3 vs 7.6 + 0.4 m/s) and lower in other ethnic groups at similar systolic (s)BPs (120mmHg) and BMIs (24.6 kg/m2). In fully adjusted regression models, independent of BP effects, Black Caribbeans, Black African and Indian young women had lower PWV (by 0.5–0.8, 95%CI 0.1–1.1 m/s) than did White UK women (6.9 + 0.2m/sec). Conversely, AIx appeared to be higher in ethnic minority groups - Indian (15.1, 13.0–17.2, %), Bangladeshi/Pakistani (15.7, 13.7–17.7, %), Caribbean (14.9, 12.3–17.0, %) and West African (15.3, 12.9–17.7, %) compared with White UK (11.9, 10.2–13.6, %), In multivariate models, adjusted for gender, central systolic BP, height and heart rate, Indian and Bangladeshi/Pakistani young adults had higher AIx (β = 3.35 and 4.20, p < 0.01) than White UK; with a similar trend for West African and Caribbeans, but not statistically significant (p = 0.08). PA, psychosocial or deprivation measures were not associated with AIx, with borderline associations from brachial BP but no other childhood variables. Conclusions: At this age AIx rather than arterial stiffness may be a useful tool for testing components of excess CV risk in some ethnic minority groups.